2008
DOI: 10.1080/03075070802049202
|View full text |Cite
|
Sign up to set email alerts
|

How are doctoral students supervised? Concepts of doctoral research supervision

Abstract: Literature about doctoral supervision has concentrated on describing the ever lengthening lists of functions that must be carried out. This functional approach is necessary but there has been little exploration of a different paradigm, a conceptual approach towards research supervision. This paper, based on interviews with supervisors from a range of disciplines, aims to fill this a gap. The main concepts identified are: Functional: where the issue is one of project management; enculturation: where the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
500
0
53

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(614 citation statements)
references
References 19 publications
21
500
0
53
Order By: Relevance
“…This raises questions concerning the supervisor's role. Lee (2008) A range of other factors may influence doctoral students' social isolation. One theme that emerged from this study is the importance of space in shaping student experiences.…”
Section: Resultsmentioning
confidence: 99%
“…This raises questions concerning the supervisor's role. Lee (2008) A range of other factors may influence doctoral students' social isolation. One theme that emerged from this study is the importance of space in shaping student experiences.…”
Section: Resultsmentioning
confidence: 99%
“…She was unhappy that she was under pressure by her department to finalise the theses. There was quite obviously a conflict between her own career interests and the success of the students (Lee, 2008).…”
Section: The Supervisory Relationshipmentioning
confidence: 99%
“…Recent studies have identified factors in research supervision promoted by experienced supervisors which contribute to student learning, such as responsiveness to students' needs and ways in which supervisorstudent relationships are maintained (e.g. de Kleijn et al 2014;Lee 2008;Mainhard et al 2009). These factors are useful for fostering supervisors' reflections on their practices and for the study of research supervision.…”
Section: Introductionmentioning
confidence: 99%